STATISTICAL METHODS TO IMPROVE THE QUALITY ASSESSMENT OF CLINICAL AUDIT RESULTS - Taras Gutor; Andriy Zimenkovsky; Zoriana Mysak (Acta Medica Leopoliensia)
The research aims at improving the quality assessment of clinical audit results in Ukraine using the complex of statistical methods and studying statistical methods in foreign reports of the clinical audit and personal experience.